Prospecting for safe (low fluoride) groundwater in the Eastern African Rift: the Arumeru District (Northern Tanzania) - G. Ghiglieri (Hydrology and Earth System Sciences, 2010)
A multidisciplinary research effort, including geological, hydrogeological, hydro-chemical, geophysical and hydrological investigations, was aimed at locating a source of safe groundwater for a district of northern Tanzania, within the western branch of the East Africa Rift Valley, where water shortage is common and much of the surface water carries unacceptable levels of dissolved fluoride. The 440 km2 study area lies in the northern part of Arumeru district and is dominated by Mt. Meru (4565 m a.s.l.). The local climate is semi-arid, with distinct wet and dry seasons. Four hydrogeological complexes were identified, occurring within different volcanic formations, either alone or superimposed upon one another. The groundwater flow system was interpreted from the spatial distribution of the springs, combined with a lithology- and geometry-based reconstruction of the aquifers. The dominant pattern consists of a multi-directional flow from the higher elevations in the south towards the lower areas in the north, but this is complicated by structures such as grabens, faults, lava domes and tholoids. After the identification of the major fluoride source, an interference pattern between groundwater and high fluoride surface water was drawn. Finally, vertical electrical soundings were performed to define the location of aquifers in regions where release of fluoride was prevented. The methodological approach for the prospecting of safe water in a semi-arid, fluoride polluted region was validated by the drilling of a 60 m deep well capable of supplying at least 3.8 l/s of low fluoride, drinkable water.